Broken Relationship Metaphors Portrayed in Taylor Swift’s Exile (2020): A Cognitive Linguistic Perspective - Meutia Rini Zahra; Deli Nirmala (Department of Linguistics, Faculty of Humanities, Diponegoro University, 2022)
Exile is a song written by Taylor Swift that describes a relationship that is no longer working on two people. This song describes a broken relationship through metaphors. This study aims to examine broken relationship metaphors in Taylor Swift’s Exile through a cognitive linguistic perspective. The method used for this research is the non-participant observation and identity referential method. The result shows that there are several metaphors that indicate a broken relationship in that song, namely [RELATIONSHIP IS A FILM], [PARTNER IS A HOMELAND], [MOVING ON IS EXILE], [OPINION IS A BREAKING BRANCH], [MOVING ON IS A SIDE DOOR], and [UNCERTAINTY IS A THIN LINE]. In conclusion, this song describes a situation of a broken relationship that is expressed in a metaphorical way to set a scene of breaking up, misunderstanding, and showing different opinions from one to another.Keywords: metaphor; exile; Taylor Swift